Introduction to psychology - Kalat, James W. (Boston, MA : Cengage, 2017)
"Drawing from the latest research and literature, Kalat's bestselling 'Introduction to Psychology' teaches you how to evaluate the evidence to separate the plausible from the scientifically demonstrable - helping you become a savvier consumer of information. Thoroughly updated, it includes expanded coverage of replicability and research misconduct, and revisits several classic topics in the light of new scholarly insight."--Provided by publisher
What is psychology? -- Scientific methods in psychology -- Biological psychology -- Sensation and perception -- Development -- Learning -- Memory -- Cognition and language -- Intelligence -- Consciousness -- Motivated behaviours -- Emotions, stress, and health -- Social behaviour -- Personality -- Abnormal psychology: disorders and treatment.
Includes bibliographical references and indexes.
Keywords: Psychology -- Textbooks; Psychology; Textbooks